The birdcage [videorecording (DVD)] - Nichols, Mike; Williams, Robin, 1951-2014; Lane, Nathan, 1956-; Hackman, Gene; Poiret, Jean, 1926-1992 (MGM Home Entertainment, 1998)
The story of a middle-aged gay couple's comic encounter with a self-righteously straight and conservative family. Armand and Albert reluctantly accept young Val's intention to marry the daughter of a conservative Senator, but when the fiancee's family comes to visit, the whole household is turned upside down.